Prevalence and Associated Factors of Malaria Infection among Outpatients Visiting Shewa Robit Health Center, Northcentral Ethiopia - Azene Tesfaye; Tadegew Teshome (Journal of Tropical Medicine)
Introduction. Malaria infection is a serious health problem killing millions in tropical developing countries including Ethiopia. The present study focused on assessing malaria prevalence and identification of determinants in Shewa Robit, northcentral Ethiopia. Methods. A cross-sectional study was conducted among 422 participants who visited Shewa Robit Health Center between 01/10/2017 and 30/04/2018, using a simple random sampling. Sociodemographic characteristics were recorded using a pre-tested semi-structured questionnaire and infection was confirmed by microscopic examination. Data were analyzed using the Statistical Program for Social Sciences (SPSS) version 20 and p<0.05 was used to indicate the level of significance. Results. Eighty-one (19.0%) microscopically confirmed malaria cases were recorded, P.vivax was the most frequently detected species (n = 58; 71.6%). Interestingly, 73.2% (n = 309) of the participant did not utilize LLINs due to the fear of toxicity (37.4%, n = 158), misconception (21.6%, n = 91), and shortage (14.2%, n = 60). The data showed age, gender, marital status, family size, usage of LLINs and application of IRS, proximity to mosquito breeding sites and less robust and porous walls were the determinants of the infection in the study area. Conclusion. The prevalence of malaria in the study population was high and P. vivax being the most common causative agent. Environmental and behavioral factors related to LLIN are the potential determinants of malaria. Continued public health interventions, targeting proper utilization of bed nets, drainage of stagnant water, and improved public awareness about reducing the risk of insect bites have the potential to minimize the infection.